The Development of Tourism Element in Lampang Province - Plangmarn, Acheraporn (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This research aims to reveal the development method of the six tourism elements in Lampang province. including lodging, restaurant, souvenir shops, transportation, environment and safety, and facilities. A sample of 384 tourists visiting the main attraction in Lampang was collected through judgment sampling. The results showed that the total tourist sample was very satisfied with Lampang tourism elements. Age, status, education, residence, travel frequency, travel occasion and number in groups were found to have a significant relationship with the tourism element satisfaction. The important elements that gained less satisfaction should be considered as the first priority for destination development, although there seemed to be different elements for each destination.